Comparative study on dermatoglyphics in patients with PTSD - Glamuzina, Ljubomir (Array, 2009)
Abstract: The factors situated at the bases of the genesis and development of PTSD are divided in: biological, psychological and social factors. Primary factor is a stressful event of extremely dangerous and threatening nature. The sort and the intensity of the stressful event too play an important role, followed by the personality structure, the relation with the environment and the genetic constitution. The study was thought to determine the quantitative dermatoglyphic properties of the digito-palmar complex in patients with PTSD aiming to establish whether there are biological, that is, genetic bases for PTSD, in what measure they determine the clinical manifestation of the disorder, and whether there is a dermatoglyphic marker, characteristic for people with PTSD.